Generalized multiuser orthogonal space-division multiplexing. - Zhengang Pan
This paper addresses the problem of performing orthogonal space-division multiplexing (OSDM) for downlink, point-to-multipoint communications when multiple antennas are utilized at the base station (BS) and (optionally) all mobile stations (MS). Based on a closed-form antenna weight solution for single-user multiple-input multiple-output communications in the presence of other receiver points, we devise an iterative algorithm that finds the multiuser antenna weights for OSDM in downlink or broadcast channels. Upon convergence, each mobile user will receive only the desired activated spatial modes with no cochannel interference. Necessary and sufficient conditions for the existence of OSDM among the number of mobile users, the number of transmit antennas at the BS, and the number of receive antennas at the MS, are also derived. The assumption for the proposed method is that the BS knows the channels for all MS's and that the channel dynamics are quasi-stationary.
Keywords: Activated spatial mode; Broadcast channel; Closed-form antenna weight solution; Cochannel interference; Generalized multiuser orthogonal space-division multiplexing; Iterative algorithm; Mobile station; Mobile user; Multiple antenna; Multiuser antenna weight; Point-to-multipoint communication; Receiving antenna; Single-user multiple-input multiple-output communication; Transmitting antenna